Androgen Receptor Regulates the Growth of Neuroblastoma Cells in vitro and in vivo - Sun, Junyan; Wang, Dongmei; Guo, Lianying; Fang, Shengyun; Wang, Yang; Xing, Rong (Frontiers in Neuroscience, 2017)
Background: Neuroblastoma is the most common extracranial tumors in children. At present about the true etiology of neuroblastoma is unclear and many studies have tried to find effective treatments for these primary malignant tumors. Although it has been illustrated that androgen receptor (AR) was expressed in neuroblastoma cells in some former reports, the biological role of androgen receptor in the development of neuroblastoma is not fully understood. Methods: Androgen (R1881) and the antagonists of androgen receptor (MDV3100 and ARN509) were used to study the role of the androgen receptor signaling pathway in vitro and in vivo on SH-SY5Y and Neuro-2a (N2a) cell lines. Results: We found that AR expression showed an R1881 dose-dependent manner in neuroblastoma cells in vitro and R1881was able to increase, while both antagonists of androgen receptor (MDV3100 and ARN509) significantly decrease, the proliferation, migration, invasion and sphere formation of SH-SY5Y and N2a cells. Moreover, androgen promoted the growth of N2a tumor in vivo. However, when androgen receptor (AR) was effectively knocked down in the two cell lines by siRNA, either promoting or inhibiting effect of the androgen or androgen receptor antagonists, respectively, was attenuated. Conclusion: Our results suggested that androgen receptor may involve in the progression of neuroblastoma as well as provided insight into a new target for the diagnosis and treatment of neuroblastoma patients.